2018
DOI: 10.1161/circimaging.117.007047
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Structural Remodeling, Longitudinal Systolic Strain, and Torsional Mechanics in Lean and Nonlean Dysglycemic Chinese Adults

Abstract: These data demonstrate the presence of preclinical cardiac remodeling and systolic dysfunction in prediabetic and diabetic Chinese adults, occurring at lower thresholds of glycemic indices than defined by international standards, particularly in lean individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 48 publications
2
30
0
4
Order By: Relevance
“…A recent meta‐analysis of 47 cohort studies, including 12 million individuals, found that the relative risks for heart failure associated with type 2 diabetes were 1.95 (95% CI 1.70–2.22) in women and 1.74 (95% CI 1.55–1.95) in men, with a pooled men‐to‐women ratio of the relative risks of 1.09 (95% CI 1.05–1.13), indicating a significant difference 59 . Women with type 2 diabetes show more pronounced adverse left ventricular remodelling (oriented toward concentric hypertrophy), and have a lower quality of life and worse outcomes compared with type 2 diabetic men, even when they have a normal body mass index (BMI) and glucose levels in the ‘pre‐diabetes’ range 60,61 …”
Section: Occurrence Of Heart Failurementioning
confidence: 99%
“…A recent meta‐analysis of 47 cohort studies, including 12 million individuals, found that the relative risks for heart failure associated with type 2 diabetes were 1.95 (95% CI 1.70–2.22) in women and 1.74 (95% CI 1.55–1.95) in men, with a pooled men‐to‐women ratio of the relative risks of 1.09 (95% CI 1.05–1.13), indicating a significant difference 59 . Women with type 2 diabetes show more pronounced adverse left ventricular remodelling (oriented toward concentric hypertrophy), and have a lower quality of life and worse outcomes compared with type 2 diabetic men, even when they have a normal body mass index (BMI) and glucose levels in the ‘pre‐diabetes’ range 60,61 …”
Section: Occurrence Of Heart Failurementioning
confidence: 99%
“…Diabetes is pandemic and is a growing healthcare burden worldwide [1,2]. Recently, lean diabetes (people with diabetes and a low BMI [<25 kg/m 2 ]) has been highlighted as an emerging pathological condition [3,4] and has been reported to have a higher mortality than excessive weight or even grade I obese diabetes [4][5][6][7]. However, people with low BMI (lean/normal weight, particularly BMI <22-23 kg/m 2 ) also had higher mortality than overweight people in the general population [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of elevated plasma glucose but with a maintained plasma insulin level in these HFD/STZ rats is consistent with insulin resistance ( Reed et al, 2000 ; Sharma et al, 2011 ; Guo et al, 2012 ). However, the lower body weight and fat mass at study endpoint compared to controls is not entirely reflective of obese T2DM ( Lin et al, 2018 ; Bai et al, 2019 ), but rather as a model of T2DM, an emerging clinical feature in many diabetic populations ( Balasubramanyam et al, 2011 ; Florez and Castillo-Florez, 2012 ).…”
Section: Discussionmentioning
confidence: 99%